Justice, Truth, and Community Organizing in Boston, MA - Barron, Melanie Ann (2012)
In 2010, community organizers in Boston, MA began to lay the groundwork for a truth and reconciliation process about the long-term impacts of the violence and racism surrounding the desegregation/busing crisis in the 1970s. Organizers believe that the busing crisis still presents impediments to the ability of communities of color in Boston to live well and participate in public life. I contextualize their efforts first as a response to the failures of the liberal democratic reforms that marked the civil rights movement. Rather than truly reforming the structures that permit the existence of racialized inequalities, I argue that the liberal democratic state instead systematically preserves and enhances white privileged access to resources. The state does this by resolving crises in such a way that places racism and inequality outside the purview of state responsibility by constructing a “post-racist” sensibility. I demonstrate this by examining two seminal court cases in Boston: Morgan v. Hennigan and Wessman v. Boston School Committee. Second, in order to achieve equality, I argue that the notions of justice and rights must be expanded in order to achieve a positive conception of rights—one in which it is possible to advocate for the rights of groups rather than liberal individuals. Thus, I conceptualize the organizers’ efforts as a way to use a restorative conception of justice to assert a Right to the City, in terms of asserting a right to live well and participate in public life